Meiteis Naming Practice - Singh, Aboy Yumnam (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This paper mainly attempts to describe the naming practice of Meiteis. Such study is an important linguistic aspect in Meitei society. It also studies the different periods of giving Meiteis personal names, the order of names and the categories of given names. The study of Meitei naming practice will give a deep knowledge insight into language of Meitei, culture, philosophy, belief, religion, thought and social changes.